(untitled) - Cohoon, James P. (Boston, 2004)
Java 1.5 Program Design is about the fundamentals of programming and software development using Java. It is targeted for a first programming course and has been designed to be appropriate for people from all disciplines. The authors assume no prior programming skills and use mathematics and science at a level appropriate to first-year college students. The breadth of coverage and the arrangement of the chapters provide flexibility for the instructor in what and when topics are introduced.
Keywords: Java (Computer program language),Java ( ngôn ngữ chương trình máy tính )